PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS POWERPOINT PADA MATA PELAJARAN EKONOMI UNTUK MENINGKATKAN MINAT BELAJAR SISWA DI SMP NEGERI 3 SATU ATAP ARAMO - Saota, Helena (Universitas Nias Raya, 2024)
This research aims to investigate the influence of implementing the Discovery Learning model based on PowerPoint on students' interest in learning economics, specifically on economic activities such as production, distribution, and consumption, at SMP Negeri 3 Satu Atap Aramo. This study employs the Classroom Action Research (CAR) approach with a qualitative method aimed at exploring the learning process in addressing specific issues. The research was conducted at SMP Negeri 3 Satu Atap Aramo with a population of seventh-grade students, totaling 20 students. The results of the research indicate that out of the total sampled students, 25% of them obtained scores ranging from 50 to 56, another 25% of students scored between 66 and 75, and the remaining 50% of students scored between 76 and 98. This research aims to provide a deeper understanding of the effectiveness of specific teaching methods on students' learning interests in the context of economics.